ISLAMIC EDUCATION POLITICS: DYNAMIC AND RELEVANCE DUTCH ETHICAL POLITICS IN INDONESIA - Dian Silvia Rozza; Tobroni Tobroni; Moh. Nurhakim (Research and Development Journal of Education, 2023)
This study discusses the dynamics and relevance of the Dutch colonial Ethical Politics for the Indonesian people. At that time, Ethical Politics was considered to be limited to the new Dutch colonial model, but the fact is that Ethical Politics has considerable relevance for education, especially Islamic education in Indonesia. This research uses a qualitative approach with a type of literature study in the form of books and journals related to politics and education in the Dutch colonial period. The results of the study show that: (1) Ethical Politics in the field of education continues to change in line with the replacement of the governor general during the Dutch colonial period. Colonialism and Dutch intervention led to the development of education from elementary schools to universities; (2) The relevance between Ethical Politics and Islamic education in Indonesia is suppressing illiteracy and producing reformers and Islamic nationalists. These figures began to establish Islamic educational institutions and Islamic organizations which still exist today.